Uso de geotecnologias para subsidiar a implantação de uma atividade econômica regional em piscicultura - Francisco, Humberto Rodrigues (2020)
Aquaculture has shown a relevant potential in the development of several regional economies in the country, especially in recent decades. However, the activity still lacks consolidated information about the productive sector, mainly to ensure its expansion, viability and sustainability, since many environmental, social and economic approaches have already been applied without standardization. Thus, the present study was conducted, to develop a methodology capable of carrying out the classification and identification of areas with aptitude to fish farming, in ground-excavated nurseries, considering the legal areas or not, and to verify the suitablement and estimate the productive potential of Nile tilapia (Oreochromis niloticus) through an intensive breeding system. This methodology was applied in three municipalities located in the center-south region of the state of Paraná, Brazil, with low Human Development Index (HDI), compared to the neighboring regions, which were not considered tilapia producers. For the classification of suitable areas, it was used in a Geographic Information System (GIS), Digital Elevation Model (DEM) data, land use and occupation and soil types. For that, a Variable Reclassification Model (MRV) was developed and the Analytic Hierarchy Process (AHP) method was applied to establish weights for multi-criteria assessment on the established factors. Restricted and unclassified fish farming areas were identified and removed from the analysis. In order to estimate the productive potential of tilapia, the mapping of the ground-excavated ponds was carried out using GIS software on high resolution satellite images. It was also verified whether the region had a favorable climate for the creation of the species. Then, the productive potential of the fish was estimated, using a density of 54 t/ha/year as a basis, and finally, a study based on directional distribution was carried out. From the results it was found that in the places classified as: “totally suitable” and “suitable”, were 33,270.79 ha (18.71%) and in contrast the restricted areas resulted in 54,427.91 ha (30.60%) of the total area. Also, it was found that the study area has a milder climate for the creation of tilapia in some months of the year, however, this does not prevent its production. When the estimated production potential for tilapia was calculated, it was verified that there is the possibility of the region slaughtering about 34.12t/fish daily, which is considered a relevant production. The use of directional distribution proved to be a suitable methodology in order to identify the determination of the trend pattern of the centroids, because it took into consideration the geolocation of the ground-excavated ponds installed, where there would be the highest density of fish being produced. It was considered that the application of geotechnologies contributed significantly to the study and the viability of tilapia production in a non-producing region. Therefore, this methodology can become a useful tool to be used in regional planning and, thus, supporting the development of public policies that encourage investments for the development of fish farming.